Associations of mortality and cardiovascular disease risks with diabetes and albuminuria in urban Indigenous Australians: the DRUID follow‐up study. Issue 7 (15th May 2017) - Barr, E. L. M.; Cunningham, J.; Tatipata, S.; Dunbar, T.; Kangaharan, N.; Guthridge, S.; Li, S. Q.; Condon, J. R.; Shaw, J. E.; O'Dea, K.; Maple‐Brown, L. J.
Abstract: Aim: To assess the relationships of diabetes and albuminuria with all‐cause mortality and cardiovascular disease outcomes in a population without prior cardiovascular disease using data from the Darwin Region Urban Indigenous Diabetes (DRUID) study. Methods: We conducted a prospective cohort study of 706 participants (aged 15–81 years, 68% women) without prior cardiovascular disease who underwent a 75‐g oral glucose tolerance test. Deaths and fatal or non‐fatal cardiovascular disease were determined over 7 years, and hazard ratios with 95% CIs and population attributable risks were estimated for baseline glycaemia and albuminuria. Results: Compared with normoglycaemia and after adjustment for age, sex, hypertension, dyslipidaemia and smoking, known diabetes was associated with an adjusted hazard ratio of 4.8 (95% CI 1.5–14.7) for all‐cause mortality and 5.6 (95% CI 2.1–15.2) for cardiovascular disease. Compared with normoalbuminuria, the respective adjusted risks for macroalbuminuria were 10.9 (95% CI 3.7–32.1) and 3.9 (95% CI 1.4–10.8). The Adjusted all‐cause mortality and cardiovascular disease estimated population attributable risks for diabetes were 27% and 32%, and for albuminuria they were 32% and 21%, respectively. Conclusions: In our study population, the burden of mortality and cardiovascular disease was largely driven by diabetes and albuminuria. This finding on the influence of diabetes and albuminuria is consistent with reports in other high‐risk Indigenous populations and should be better reflected in risk scores and intervention programmes. What's new?: The Darwin Region Urban Indigenous Diabetes (DRUID) follow‐up study is one of the few studies to assess the prospective associations of diabetes and albuminuria on mortality and cardiovascular disease (CVD) in an urban Indigenous population. We showed that nearly a third of CVD events in our study population were attributable to diabetes and 21% were attributable to albuminuria. Public health initiatives that aim to prevent and better manage diabetes and renal disease could have a substantial impact on the burden of CVD in Indigenous Australians.